Norbert Is Nosy - Ellen Weiss (U.S.A A Golden Book, 1999)
Sometimes Norbert's nosiness leads to interesting discoveries--and sometimes to trouble. Finally, Norbert realizes that if he's a bit more careful with his curiosity, he'll definitely have a lot more fun.
Keywords: Non-fiction -- Non-fiction